Epidemiological profiles and pathogenicity of Vancomycin-resistant Enterococcus faecium clinical isolates in Taiwan - Pei-Yun Lin; Shang-Yih Chan; Arnold Stern; Po-Hsiang Chen; Hung-Chi Yang (PeerJ, 2023)
The emerging Vancomycin-resistant Enterococcus faecium (VRE-fm) is an opportunistic pathogen causing nosocomial infections. The identification of VRE-fm is important for successful prevention and control in healthcare settings. VRE-fm clinical isolates obtained from regional hospitals in northern Taiwan were characterized for antimicrobial susceptibility, virulence genes and biofilm production. Most isolates exhibited multi-drug resistance and carried the virulence genes, esp and hyl. While all isolates produce biofilms, those isolates that carried esp exhibited greater biofilm production. Isolates with different virulence gene carriages were examined for pathogenicity by using a nematode model, Caenorhabditis elegans, for determining microbial-host interactions. The survival assay showed that C. elegans was susceptible to Linezolid-resistant VRE-fm isolates with hyl. Combining the molecular epidemiological profiles regarding pathogenesis in C. elegans can serve as a guide for physicians in limiting opportunistic infections caused by VRE-fm.